The unfolding story of a redox chaperone - Mayer, Matthias P. (Cell, 2012)
Oxidative stress, especially in combination with heat stress, poses a life-threatening challenge to many organisms by causing protein misfolding and aggregation. In this issue, Reichmann et al. demonstrate how a destabilized linker region of the bacterial chaperone Hsp33 prevents aggregation of a denatured protein by stabilizing structural elements.
Gesehen am 02.11.2018